Technology, automation and productivity of stock exchanges: International evidence - Iftekhar Hasan; Markku Malkamäki; Heiko Schmiedel (Bank of Finland, 2002)
The paper stresses on the importance of understanding the operational choices, strategies, and performances of stock exchanges as regular operating firms (Arnold et al (1999), and Pirrong (1999)) Using unbalanced panel data on 49 stock exchanges over the period 1989 1998, the paper traces the productivity of stock exchanges over time and across different types and groups of exchanges.We find significant variability in respect of the productivity revenue and cost efficiency across these exchanges.On average, North American exchanges are found to be most cost and revenue efficient.However, our findings also indicate that European exchanges have improved the most, in respect of cost efficiency, while exchanges in South America and Asia-Pacific regions are found to be lagging as regards both cost and revenue estimations.The evidence also indicates that investment in technology-related developments effectively influenced cost and revenue efficiency.Moreover, organisational structure and market competition are found to be significantly associated with both cost and revenue efficiency for the exchanges studied, whereas market size and quality are related only to revenue efficiency.
URN:NBN:fi:bof-20140807631
Keywords: C23; O50; 330; stock exchanges; technological progress; technical efficiency